Community Involvement and Perceptions of the Community-Based Health Planning and Services (CHPS) Strategy for Improving Health Outcomes in Ghana: Quantitative Comparative Evidence from Two System Learning Districts of the CHPS+ Project. (7th May 2020) - Kweku, Margaret; Amu, Hubert; Adjuik, Martin; Manu, Emmanuel; Aku, Fortress Yayra; Tarkang, Elvis Enowbeyang; Komesuor, Joyce; Asalu, Geoffrey Adebayo; Amuna, Norbert Ndaah; Boateng, Laud Ampomah; Alornyo, Justine Sefakor; Glover, Roland; et al.
Abstract : Background . The Community-based Health Planning and Services (CHPS) initiative is Ghana's flagship strategy for achieving universal health coverage (UHC). Community involvement in and perceptions of CHPS capacity to improve health outcomes of communities are examined. Methods . This community-based descriptive cross-sectional study recruited 1008 adults aged 18 years and above in two System Learning Districts of the CHPS+ project. Data collected were analysed using descriptive and inferential statistics. Results . The level of community involvement in CHPS activities was 48.9% of the population studied. The overall level of positive perception of CHPS services was 51.7%. Community members who were involved in identifying resources (AOR = 1.86 (95% CI = 1.17, 2.97), p = 0.009 ), organising durbars (AOR = 2.09 (95% CI = 1.12, 3.88), p = 0.020 ), and preparing sites for outreach services (AOR = 3.76 (95% CI = 2.23, 6.34), p < 0.001 ) were significantly more likely to have positive perceptions of the relevance of CHPS to improving the health status of communities compared to those who were uninvolved. Conclusion . The level of community involvement in CHPS services is low. Ghana may not be able to attain the UHC goal by 2030 through CHPS implementation unless its level of community involvement is markedly improved. Ghana's health sector stakeholders should implement community engagement mechanisms that foster improved worker outreach, expanded use of community gatherings, and more active participation of traditional leaders and grassroots political representatives.